139. Social Support Decreases No-Show Rates Among Patients with Injection-Drug-Use-Related Infections and Opioid Use Disorder. (4th December 2021) - Grubbs, James A; Blevins, Sarah R; Weeks, Ryan; Stivers, Tiffany; Sabitus, Kathryn; Thornton, Alice
Abstract: Background: Opioid overdose is the leading cause of injury-related death in the United States. Kentucky ranks in the top 5 states for overdose death and has one of the highest rates of acute hepatitis C (HCV). Fifty-four of Kentucky's counties are among the 220 U.S. counties identified as high risk for rapid dissemination of HIV and HCV. Poverty, legal issues, and transportation are barriers to effective treatment of opioid use disorder (OUD) and related infections. The WRAP project (Wrap-around Recovery for Addiction and infectious Diseases project) is an ongoing multi-disciplinary program to expand access to OUD treatment at University of Kentucky HealthCare. This program provides social support including transportation assistance, case management, and counseling. Missed visits have been associated with multiple adverse outcomes. Methods: We compared missed infectious diseases clinic visits (n=620) of patients enrolled in WRAP to those of patients who were referred and eligible, but not enrolled using chi-square tests for odds ratios. Results: We enrolled 35% of eligible, referred patients. The majority (70%) of patients not enrolled were referred while inpatient and discharged before they could be enrolled. WRAP-enrolled patients missed 21% of visits, whereas WRAP-eligible, non-enrolled patients missed 31% of visits (OR 0.59, 95% CI 0.49 to 0.72, p-value < 0.001), Figure 1. This finding was consistent for WRAP-referred patients with a diagnosis of HIV who were also eligible for Ryan White support services: WRAP-enrolled patients missed 17% of visits and WRAP-eligible, non-enrolled patients missed 25% of visits (OR 0.26, 95% CI 0.20 to 0.35, p-value 0.002). For HCV patients who were mostly referred as outpatients, WRAP-enrolled patients missed 25% of visits while WRAP-eligible, non-enrolled patients missed 39% (OR 0.54, 95% CI 0.41 to 0.72, p-value 0.0003), Figure 2. Figure 1. ID clinic visit attendance among WRAP eligible, non-enrolled and WRAP enrolled patients. WRAP-enrolled patients missed 21% of visits, whereas WRAP-eligible, non-enrolled patients missed 31% of visits (OR 0.59, 95% CI 0.49 to 0.72, p-value < 0.001). Figure 2. ID clinic attendance among WRAP eligible, non-enrolled and WRAP enrolled patients with HIV and hepatitis C primary diagnoses. A. WRAP-enrolled patients with a primary diagnosis of HIV missed 17% of visits and WRAP-eligible, non-enrolled patients missed 25% of visits (OR 0.26, 95% CI 0.20 to 0.35, p-value 0.002). B. WRAP-enrolled patients with a primary diagnosis of hepatitis C missed 25% of visits while WRAP-eligible, non-enrolled patients missed 39% (OR 0.54, 95% CI 0.41 to 0.72, p-value 0.0003). Conclusion: Providing patients with social support services to address barriers to attending clinic visits was associated with fewer missed ID clinic visits. Higher engagement in care is a step towards implementing evidence-based treatment to lessen overdose deaths and injection-related infections. Future projects will include investigating whether WRAP enrollment is associated with fewer hospital admission and ER visits. Disclosures: All Authors : No reported disclosures